Integração regional e fronteiras: desafios para a governança das migrações internacionais na América Latina - Baeninger, Rosana (2016)
The article analyzes the increasing migratory movements within the context of South American regional integration processes and the new South-South migration contours. It intends to present the Latin America and Brazil’s border migration scenario in the framework of the regulatory immigration policies as adopted by the Brazilian State. The 1980 legal landmark, the “Estatuto do Estrangeiro”, proves to be inappropriate for the current context in which Brazil is the main immigrant destination in South America, as well as the regional integration leader. Thus, it discusses the problematic of “migratory governability”, along with the concepts of regulation policyand immigrant policy, in order to analyze the relation between regional integration and international migration. It also highlights the immigrant flux straddling borderlines, its expansion, and the broadening of migration spaces in the regional integration scope.